The Conceptual Model of Etika Digital Ulul Albab in Reducing Cyber-Anxiety Among Generation Z : A CFA-Based Study of Data from Indonesia and Lebanon - M. Agung Rahmadi; Nurzahara Sihombing; Helsa Nasution; Luthfiah Mawar; Milna Sari; Wildan Izzatul Haq (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2025)
This study designs and empirically tests the validity of the conceptual model of Etika Digital Ulul Albab as a form of psychological intervention aimed at reducing cyber-anxiety levels among Generation Z, drawing on data encompassing populations in Indonesia and Lebanon. Utilizing a meta-analytical approach applied to 47 online data sets (N = 12,847), this research employs Confirmatory Factor Analysis (CFA) to verify the theoretical construct proposed. The results indicate an excellent model fit (χ²/df = 2.14, CFI = 0.96, TLI = 0.95, RMSEA = 0.048, SRMR = 0.041). Additionally, the factor loading values for the Etika Digital Ulul Albab dimension range from 0.72 to 0.89, with a composite reliability of 0.93, indicating high internal consistency. Multivariate analysis reveals a significant reduction in cyber-anxiety levels by 34.2% (p < 0.001) in the Indonesian group and by 31.8% (p < 0.001) in the Lebanese group. Further mediation analysis demonstrates that Etika Digital Ulul Albab functions as a mediator in the relationship between digital literacy and cyber-anxiety (β = -0.452, p < 0.001). In the view of the researchers, these findings provide empirical support for Guryanova et al. (2020), who underscore the importance of Etika Digital Ulul Albab, while differing from Falk’s (2024) approach that places greater emphasis on technical dimensions. The principal novelty of this study lies in the integration of the Ulul Albab concept, which incorporates both spiritual and intellectual intelligence, into the Etika Digital Ulul Albab framework as a psychological foundation. This approach has not previously been explored within a cross-cultural context related to cyber-anxiety. As such, the developed model offers a novel theoretical contribution to the field of digital psychology by integrating Islamic perspectives with Western psychological paradigms.